(untitled) (Al-Academy, 2023)
Fine art represents part of society’s culture. The development of art was accompanied by the penetration of new worlds known as the fourth dimension. After art entered the boundaries of geometry and reduction; He began to break into the absurd, and the form and philosophy of art changed, moving from modernity to what came after it to contemporary. Transforming from a formal form into a symbolic form with philosophical implications linked to the light, audio and kinetic effects as they embody time, the concept became the master of the idea. The research aims to identify the concept of time and its types, then the philosophical concept of time and its reflection on contemporary art, through the analytical study of a selection of contemporary arts based on investigating the philosophy of time.